Direitos humanos e teatro do oprimido [manuscrito] : uma aproximação dialógica - Sousa, Rogério Newton de Carvalho (2011)
This research shows the thread of Ariadne which links human rights and the theater of the Oppressed. It chooses to place them in the world of life using the tragedies of the century of Pericles and the Law visions of Flores, Bobbi ,Ost and Dworki , in search of the political dimension of human experience and the political and social character of the judicial phenomenon. The human rights are presented in the historical context of modernity in connection with the enlightenment thought. Pursuing the contagion between the Law and the historical aspects of individual and collective experiences, one of the main theoretical axes is a critical and realist theory of the human rights of Flores. Starting with Boal s assertion that every theater is political, and that a citizen is not only the one who lives in society, but the one who transforms it, this study visits its critical revision of the Western theater from Aristotle to Brecht as a reflexive base for identifying the main political and cultural ideas that guided the creation of the Oppressed Aesthetics : Impure Ganga - the theater of the Oppressed is inserted in the historical context that presided its genesis, evidencing the political engagement of the left side. The influences about the pedagogical character are captured in authors such as Marx, Freire and Brecht. Originated in the society, human rights and the theater of the oppressed are attracted to each other but by the critical capacity of the theater and literature, they also repel each other under the sign of non acceptance . The dialogue between both elects the political aspect as theme and counter hegemonic theory and practice. It presents the plurality of routes as methodological place in which the distinctive conception of human dignity and rights are legitimate. This fact points to a joint authorship instead of an exclusive affiliation to the Western modernity. The art is taken as a measuring criterion of axiological progress or retrocess. The a priori universalism of the Universal human rights declaration is questioned through the perspective that such rights are historical constructed and not given artifacts. Resistance to oppression, political participation and democratic transitivity are common characteristics of human rights and of the theater of the Oppressed. The idea of revolution is revisited under the counter -hegemonic prism in the visions of Flores and in the joint revolution of Morin. A society without the oppressed and the oppressors and an ethical horizon are very dear characteristics to the human rights and to the theater of the oppressed evidencing the responsibility as the ethics by excellence of both.